Creative Serbia and AI: Potential of Shaping Creative Generative Artificial Intelligence in Arts of the Future through the Example of Midjourney/Discord Application - ZDRAVKOVIĆ, ŽELJKO (Napredak, 2024)
The paper aims to investigate how artificial intelligence (AI) can shape the future of artistic creativity in Serbia. This analysis will focus on the potential of new algorithmic tools of creative generative AI, more specifically on applications such as Midjourney/Discord, as well as the specific examples and possibilities of artistic expression that they certainly open up. The integration of AI and art opens up new possibilities for creators and audiences, but at the same time raises questions about authenticity, originality and the role of the artist. Moreover, this paper will explore how AI technology affects the process of creating works of art, audience perception and cultural implications. Through an interdisciplinary approach that combines art, technology and social sciences, this paper will provide insight into the potential and challenges brought by the integration of artificial intelligence into art, especially in the context of creative Serbia.